Do different halal certificates have different impacts on Muslims? A case study of Malaysia / Yukichika Kawata and Syed Ahmed Salman - Kawata, Yukichika; Salman, Syed Ahmed (Universiti Teknologi MARA, 2020)
Muslims whether practicing Islam or not but they are sincerely concerned about halal food. Halal is one of the most primary concepts for Muslims. With a rising number of the Muslim population worldwide, halal has become a vital concern among enterprises. Halal can be interpreted as permissible or lawful. In the Holy Quran, Allah orders Muslims and all of humankind to eat anything halal to the Shari'ah'. The halal is one of the most essential concepts for Muslims and many associations worldwide issue halal certificates of their own. This study investigated in what ways Muslims treat different halal certificates using instant coffee as an example. If Muslims perceive different values for different halal certificates, it means that they regard halal certificates more like a commercial certificate. On the other hand, if they perceive almost the same value for different halal certificates, they regard the certificate as a religious certificate. To investigate which is more relevant, the choice experiment was conducted to gather data in Malaysia. Then, a conditional logit model was applied to estimate willingness to pay for packed instant coffee of the same company produced in 6 different countries (with/without the halal certificate logo of the produced country). The results showed that although Malaysian Muslims were not familiar with halal certification logos except for the Malaysian halal logo, they perceived almost the same values for halal certificates from 6 different countries, indicating that they regarded different halal certificates in the same way. This result implied that Muslims found the halal concept as a religious concept and not as a commercial one.